Strategic Knowledge for Social Participation in Unified Health System - Renata Lopes De Siqueira; Rosângela Minardi Mitre Cotta; Jeferson Boechat Soares (O Mundo da Saúde)
Social participation in the Unified Health System (UHS) requires essential technical skills. This paper aims to evaluate the grasp of information by the members of Municipal Health Council of Viçosa, Minas Gerais. By the means of triangula- tion of the methods, which include participative observation, semi structured interview and documental analysis, it was assessed the knowledge of the counselors on juridical and technical-administrative documents, relative to the regulation and management of UHS. Additionally, we proceeded to survey the number of mandates, attendance at meetings and par- ticipation in workshops for Training of Health Counselors. The collected data reveals iniquity in the grasp of information, whose causes refer to: the bureaucratic character attributed to the normative instruments, the highly technical encoded format; the absence of technical support; the poor infrastructure and incipient knowledge of virtual technologies to access information. Also, it was noticed the occurrence of a political culture, in which there is fluctuations of: authoritarianism; defense of private interests in political settings; omission and/or indifference in relation to collective causes. It concludes the need for continuing education of counselors with a view to consolidating the social participation. To neglect the urgency of continuing education enables holders of political power perpetuate their authoritarian practices, which are incompat- ible with the real demands on public health. However, the overcoming of such practices requires adopting a critical and reflective teaching model, in which, besides the transfer of key information about the normative content that counselors need to master for the exercise of their duties, there is the promotion of a culture of democratic political participation; and resistance to authoritarianism and clientelism, as both of the latter are common in the Brazilian political system, especially in small and medium-sized municipalities.